On some interesting opisthobranchs (Mollusca, Gastropoda) from the Azores - Fontes, Jorge (2020)
The nudibranch Eubranchus farrani Alder and Hancock, 1844 is recorded from the Azores for the first time. The presence of the sacoglossan Placida cremoniana (Trinchese, 1892) in the Azores is confirmed. Pleurobranchus sp. from the Azores, Madeira and the Canary Islands is compared with P. garciagomesi Cervera et al. 1996; it probably is an undescribed species.